Forms of Female Masculinity Power in the Novel Women Waiting in the Hallway to the Sea by Dian Purnomo - Fatimatus Zahro; Taswirul Afkar; Engkin Suwandana (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study examines the representation of the power of women's masculinity in the novel Women Who Wait in the Aisle to the Sea by Dian Purnomo. The research problem focuses on how forms of masculinity power are displayed through female protagonists and how these characteristics reflect the configuration of masculinity according to Raewyn W. Connell's theory. This research aims to uncover how female characters build power, resistance, and independence through masculine attributes in the context of oppressive social structures. The method used is qualitative descriptive with reading and recording techniques as well as content analysis of novel texts. The results of the study show that Shalom figures represent the power of masculinity through courage, social dominance, mental toughness, rhetorical leadership, and physical endurance. These findings prove that women in literary narratives are able to internalize masculine attributes as a resistance strategy against social injustice. The conclusion of this study is that women's forms of masculinity power not only challenge conventional gender stereotypes, but also expand the understanding of women's roles in social structures through powerful and empowered literary representations.